These few precious days : the final year of Jack with Jackie - Andersen, Christopher P. (Gallery Books, 2013)
An account of Jack and Jackie Kennedy's final year together reveals details of their complex marriage, including rumored infidelities, the president's hidden medical problems, and the tragic death of their infant son.